2001
DOI: 10.1159/000046903
|View full text |Cite
|
Sign up to set email alerts
|

Localization, Physiological Significance and Possible Clinical Implication of Gastrointestinal Melatonin

Abstract: The gastrointestinal tract (GIT) is a major source of extrapineal melatonin. In some animals, tissue concentrations of melatonin in the GIT surpass blood levels by 10–100 times and the digestive tract contributes significantly to melatonin concentrations in the peripheral blood, particularly during the day. Some melatonin found in the GIT may originate from the pineal gland, as the organs of the digestive system contain binding sites, which in some species exhibit circadian variation. Unlike the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
115
1
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 132 publications
(239 reference statements)
1
115
1
7
Order By: Relevance
“…In fact, already early investigations indicated the possibility of such rhythms in the digestive tract of rats [3] and pigeons [30]. But the extent of variation was consistently much lower in the gut than the pineal gland or the peripheral circulation [4,23], and sometimes rhythmicity was not readily detectable but see [30]. Since the amounts of total gastrointestinal melatonin are up to orders of magnitude higher than those found in the pineal [4][5][6]12,15], the contribution of this extrapineal source to the levels of circulating melatonin is of conside-rable interest.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, already early investigations indicated the possibility of such rhythms in the digestive tract of rats [3] and pigeons [30]. But the extent of variation was consistently much lower in the gut than the pineal gland or the peripheral circulation [4,23], and sometimes rhythmicity was not readily detectable but see [30]. Since the amounts of total gastrointestinal melatonin are up to orders of magnitude higher than those found in the pineal [4][5][6]12,15], the contribution of this extrapineal source to the levels of circulating melatonin is of conside-rable interest.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10]) is here applied to melatonin, usually regarded as the hormone of the pineal gland, but also synthesized by various extrapineal tissues [12,15,23,25,26]. Among those, the digestive tract represents a system which contains by far the highest amount of this indoleamine [4][5][6]15,23]. Melatonin has properties of an antiinflammatory and antioxidant agent and is a modulator of the immune system, acid secretion and smooth muscle tone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melatonin plays a fundamental role in the neuroimmunoendocrine system [7] . The levels of melatonin and melatonin receptors are highly concentrated in the intestine [8] ; melatonin concentrations in the gut are 10-100 times greater than those found in the plasma [9] . Moreover, it has been suggested that the intestine is the major site for extra-pineal melatonin production [10] .…”
Section: Introductionmentioning
confidence: 95%